Development of multivariable control systems - Maung Maung Latt. (2009)
This dissertation presents three decentralized control systems for the three distillation systems in the literature. The loop pairing and controller design methods are: 1. RGA based Biggest Log Modulus Tuning (MLT) method 2. dRI base Skogestad internal Model Control (SIMC) method 3. ERGA based PID control method Firstly, we discuss the basic theory of a distillation column. In this dissertation, we assume that we have the transfer function models for the processes to be controlled. Then we present the usefulness of decentralized control system and, explain loop pairing methods and the controller design methods in detail. We create programming codes and block diagrams to simulate the decentralized control systems using Matlab/Simulink application software. We also discuss performance analysis for each control method using IAE, ISE, and ITAE. Finally, the simulation results from this small work can result in the invaluable conclusion and recommendation for the decentralized control system.